Radiation-Induced Peripheral Malignant Nerve Sheath Tumor Arising from Vestibular Schwannoma after Linac-Based Stereotactic Radiation Therapy: A Case Report and Review of Literatures - Putipun Puataweepong; Taweesak Janwityanujit; Noppadol Larbcharoensub; Mantana Dhanachai (Case Reports in Medicine)
In recent years the use of stereotactic radiation for vestibular schwannomas has increased worldwide. However, malignant transformation associated with radiation, although uncommon, has been reported in recent publications. We present a case of the 34 year-old female who had left vestibular schwannoma and who underwent surgery and postoperative stereotactic radiotherapy (SRT), hypofraction in 2005. At 6 years after SRT, the patient came with left facial palsy and severe headache. CT brain revealed progression in size with cystic and hemorrhagic changes of the preexisting tumor at left CPA with new obstructive hydrocephalus. Partial tumor removal was done, and the pathological report was malignant peripheral nerve sheath tumor (MPNST). Regarding the uncertainty of carcinogenesis risk, we should still practice radiation therapy with caution, especially in the young patient with tumor predisposition syndrome. Because of low incidence of MPNST after radiation, it should not be a major decision about giving radiotherapy. However, with the poor prognosis of MPNST, this possibility should be explained to the patient before radiation treatment option.